Konsep Penyeleseian Perselisihan Hubungan Industrial di Pengadilan Hubungan Industrial (PHI) Dalam Perkara Pemutusan Hubungan Kerja - Dwihardiani, Via; Rizal, Muhamad; Natari, Sari Usih (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study aims to analyze the application of the articles in Law Number 2 of 2004 regarding the settlement of industrial relations disputes in termination of employment at the Industrial Relations Court (PHI). Second, the application of the articles in Law Number 13 of 2003 related to employment in resolving compensation issues for laid-off workers at the Industrial Relations Court (PHI). The results of the study show that (1) workers or laborers who experience termination of employment by the company where they work are entitled to severance pay and compensation pay in accordance with Law Number 2 of 2004 concerning the settlement of industrial relations disputes. The role of the industrial relations court here is that through a fair decision a judge can give his decision to obtain an agreement in resolving disputes that has legal certainty. (2) Based on Law Number 13 of 2003 concerning Manpower, it is stated that for workers who receive termination of employment, they receive compensation for rights and severance pay where before the termination of employment by the company, workers or labor unions, and the government try not to terminate the employment relationship. Work.